Strategic Human Resources Technologies : Key to Managing People - Chanda, Ashok, Khrisna, B. Sivarama (Response, 2007)
n recent years, technology has transformed human resource management (HRM). While the task of managing people in organizations is becoming ever more complex, HR professionals can now get better results with the help of new tools and techniques. This pioneering and unusual book defines HR techniques as technologies in their own right, and consolidates a broad array of strategies to provide a holistic view of people management.